Surface activity in drug action - Srivastava, R. C. (Studies in interface science, 2005)
Surface activity is present in living systems; for example in body fluid or cell soup and molecules of surface-active nature are crucial to living matter and its organization. Surface Activity in Drug Action proposes "a liquid membrane hypothesis of drug action" for surface-active drugs. Chapters 1-7 contains an account of the hypothesis and chapter 8 contains a general account of the application of surface activity in therapeutics. The methodology and presentation of the information makes Surface Activity in Drug Action valuable reading for students and researchers interested in surface activity. * Is clearly written * Includes contributions from prominent names in the field, such as Bhise and Subrahmanyam * Contains a general account of the application of surface activity in therapeutics